Methodological Aspects of Estimation of ICT-Based Economic Development - ALIYEV, Alovsat G. (Management Dynamics in the Knowledge Economy, 2018)
This article is dedicated to methodological aspects of estimation of ICT-based economic development. İnformation economy development and formation trends in leading foreign countries are analyzed. A comparative analysis of the strategies and trends that form the information economy of Azerbaijan with the developed countries is carried out. In the article comparative analysis of different indicator systems in accordance with formation and assessment of development level of information and knowledge economy is given. Some recommendations about the elimination of problems existing in this field are given. A methodic for calculating Gross Domestic Product (GDP) which forms at the expense of information and knowledge is suggested. A composite index and forming indices, subindices, and indicators system of information and knowledge economy are developed.